Trypanocidal activity of four sesquiterpene lactones isolated from Asteraceae species - Elso, Orlando German (2020)
The sesquiterpene lactones eupatoriopicrin, estafietin, eupahakonenin B and minimolide have been isolated from Argentinean Astearaceae species and have been found to be active against Trypanosoma cruzi epimastigotes. The aim of this work was to evaluate the activity of these compounds by analyzing their effect against the stages of the parasites that are infective for the human. Even more interesting, we aimed to determine the effect of the most active and selective compound on an in vivo model of T. cruzi infection. Eupatoriopicrin was the most active against amastigotes and tripomastigotes (IC50 = 2.3 µg/mL, and 7.2 µg/mL, respectively) and displayed a high selectivity index. This compound was selected to study on an in vivo model of T. cruzi infection. The administration of 1 mg/kg/day of eupatoriopicrin for five consecutive days to infected mice produced a significant reduction in the parasitaemia levels in comparison with non-treated animals (area under parasitaemia curves 4.48 vs. 30.47, respectively). Skeletal muscular tissues from eupatopicrin-treated mice displayed only focal and interstitial lymphocyte inflammatory infiltrates and small areas of necrotic; by contrast, skeletal tissues from T. cruzi infected mice treated with the vehicle showed severe lymphocyte inflammatory infiltrates with necrosis of the adjacent myocytes. The results indicate that eupatoriopicrin could be considered a promising candidate for the development of new therapeutic agents for Chagas disease.